IDENTIFYING THE COMMUNICATION NEEDS OF TEACHERS IN NORTH GORONTALO SPECIAL EDUCATION SCHOOLS FOR STUDENTS WITH HEARING IMPAIRMENTS - Putri Aulya Hasan; Akroyanto Hasan; Qiran; Imam Mashudi (LPPM UNiversitas Bina Mandiri Gorontalo, 2025)
Children with special needs, particularly those with hearing impairments, require highly specialized educational environments that adapt to their unique linguistic and physiological profiles. Effective instructional delivery in these settings depends heavily on the communication efficacy of educators. This qualitative case study aimed to identify and describe the comprehensive communication needs of special education teachers in North Gorontalo. Data were gathered through semi-structured interviews, classroom observations, and documentation analysis involving active special education teachers. The thematic content analysis revealed that teachers face severe pedagogical barriers due to the lack of subject-specific standardized sign language codes and a lack of advanced professional training, which often forces lessons into passive, one-way interactions. To address these gaps, educators explicitly identified the need for continuous in-service linguistic training, the collaborative development of technical sign lexicons, and the deployment of digital assistive technologies, alongside functional audiometric equipment. Furthermore, the findings indicate that school-based learning communities (Kombel) and structured parental collaboration are vital to reinforcing alternative communication methods and enhancing students' social participation. This study provides an empirical foundation for curriculum planners to design targeted interventions that directly support special education classrooms.